Internationalization of higher education in the context of emerging economies: facing challenges and implementing policies by brics countries - Liu, Ti; Hassan, Aminuddin; Mohd Anuar, Mohd Ashraff (Human Resource Management Academic Research Society, 2023)
Purpose- Since the 1980s, internationalization of higher education has moved from the "periphery" to the "core" of higher education policy discourse. In terms of the interest preference for development, it has also shifted from the political interest preference in the early stage to the compound preference for political, economic and cultural interests, and the form of practice has also evolved from the single-threaded mechanism of internationalization of curricula and exchange of visits by academic staff in the early stage to the systematic development mode of project system and platform as the basic features. In view of the diversity of practices and methods of internationalization of higher education, as well as the diversity of understanding of 2 the nature of internationalization of higher education, the terminology related to internationalization of higher education is endless and complicated, but the core theories have not been sufficiently developed. This conceptual study is to explore the evolving concept of internationalization of higher education and its importance in emerging countries like BRICS through the literature of recent academic evidence. Methodology –A qualitative research methodlogy was employed which involve literature review of subject under investigation. The recent literature from 2018 to 2023 was investigated. Significance –Higher education institutions, particularly those located in countries that are still in the process of emerging economies, such as BRICS countries, have an immediate and urgent need to focus on the reality of the internationalization of higher education (IHE) and the associated repercussions on the sector. The main purpose of this research investigates the challenges, risks, and opportunities and also expresses the policies which establish to enhance the IHE. The finding shows that the BRICS nations should prioritize innovation, availability, and inclusivity while also encouraging scholarly collaborations and cross-cultural engagement. By pursuing these objectives, the BRICS nations may improve their international competitiveness and help the globe become more dynamic and integrated.